STRENGTHENING THE ARABIC LANGUAGE ENVIRONMENT THROUGH MADRASAH MANAGEMENT - Fauziah Bachtiar; Muhammad Almardhi (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This article aims to examine the strengthening of the bi’ah lughawiyah (Arabic language environment) through madrasah management in supporting the effectiveness of Arabic language learning. This study employs a library research method with a descriptive-qualitative approach by collecting data from various literature sources such as books, scientific journals, articles, and documents relevant to Islamic educational management and Arabic language learning. The results of the study indicate that the success of establishing a bi’ah lughawiyah is influenced by the role of madrasah management, which includes planning language programs, organizing language activities, implementing Arabic language habituation, and continuously evaluating the programs. In addition, the support of madrasah principals, teachers, and the educational environment are important factors in creating an active and communicative language atmosphere. Strengthening the bi’ah lughawiyah not only improves students’ Arabic language skills but also forms an Islamic academic culture within the madrasah environment. Therefore, well-directed and systematic madrasah management becomes one of the main keys to optimizing Arabic language learning in the era of contemporary education